Coordinated secondary control for autonomous hybrid three-port AC/DC/DS microgrid - Jin, Chi (2019)
This paper presents a coordinated secondary control (CSC) strategy for distributed power management for an autonomous hybrid three-port AC/DC/DS microgrid. The proposed CSC is on top of a generalized primary control (GPC), which consists of local power sharing (LPS) control within an individual AC or DC subgrid, global power sharing (GPS) control throughout the AC/DC subgrids, and storage power sharing (SPS) control in a distributed storage (DS) network. The CSC along with the GPC uses the local frequency/voltage deviations and offers decentralized power management with enhanced overall reliability. To eliminate the inherent frequency/voltage deviations in GPC and restore to their nominal values, a secondary control is normally applied to all distributed generators (DGs), which would degrade the performance of decentralized power management. To overcome this concern, a CSC strategy is proposed to concurrently restore frequency/voltage and re-establish a distributed power management by means of limited information exchange through the low-bandwidth communication links. The proposed control scheme has been verified by both simulations and controller hardware-in-the-loop (CHIL) experiments in an OPAL-RT digital simulator system.